Concise encyclopedia of bioresource technology - Pandey, Ashok (Food Products Press, 2004)
The Concise Encyclopedia of Bioresource Technology is a unique resource for state-of-the-art research findings on biotechnological innovations and their potential for commercial exploitation. This comprehensive reference gives you immediate access to information on the application of bioresource technology as it relates to industrial, food, and environmental biotechnology. Practitioners, academics, and researchers representing a wide range of disciplines examine vital issues including the production and applications of microbial enzymes and organic acids, fermentation, wastewater treatment, an.